2017
DOI: 10.1002/jum.14366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neonatal Brain Parenchyma Using 2‐Dimensional Shear Wave Elastography

Abstract: This study shows that differences between brain stiffness values in preterm and term neonates can be shown by using 2-dimensional shear wave elastography, and the results may be reference points for evaluating neonatal brain stiffness in research on patients with various illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 32 publications
3
32
1
1
Order By: Relevance
“…Ultrasound based cerebral elastography has recently been applied to neonates via the fontanelles without the obstruction caused by the skull 38 . Thalamus and periventricular white matter were found to be significantly lower in stiffness in the preterm group compared with the term group 39 . In adults, ultrasound elastography was successfully applied after skull opening for the assessment of neurological tumors and for reporting healthy-tissue values in agreement to MRE 40 .…”
Section: Introductionmentioning
confidence: 76%
“…Ultrasound based cerebral elastography has recently been applied to neonates via the fontanelles without the obstruction caused by the skull 38 . Thalamus and periventricular white matter were found to be significantly lower in stiffness in the preterm group compared with the term group 39 . In adults, ultrasound elastography was successfully applied after skull opening for the assessment of neurological tumors and for reporting healthy-tissue values in agreement to MRE 40 .…”
Section: Introductionmentioning
confidence: 76%
“…They found that the elasticity of gray matter in the cerebral cortex was higher than in other regions, the elasticity of the caudate nucleus was lower than in different areas; they found no significant gender difference in the elasticity of the brain region. Albayrak and Kasap found that using 2D-SWE could show differences in brain elasticity values between preterm and term neonates [11].…”
Section: Discussionmentioning
confidence: 99%
“…No adverse effects have been reported in neurosurgical investigations, where the protective skull had been removed [11]. Furthermore, uBPE has been applied in neonates without any side effects [17]. Considering this, there were no ethical concerns from the members of the institutional review board.…”
Section: Safety Considerationsmentioning
confidence: 96%